MicroRNA‐126 regulates the induction and function of CD4+ Foxp3+ regulatory T cells through PI3K/AKT pathway. Issue 2 (10th January 2013) - Qin, Andong; Wen, Zhenke; Zhou, Ya; Li, Ying; Li, Yongju; Luo, Junmin; Ren, Tao; Xu, Lin
Abstract Recent evidence showed that limited activation of PI3K/Akt pathway was critical for induction and function sustainment of CD4+Foxp3+ regulatory T cells (Tregs). However, the underlying mechanism remains largely unknown. In this study, we reported that miR‐126 was expressed in mouse and human Tregs. Further study showed that silencing of miR‐126 using miR‐126 antisense oligonucleotides (ASO) could significantly reduce the induction of Tregs in vitro. Furthermore, miR‐126 silencing could obviously reduce the expression of Foxp3 on Tregs, which was accompanied by decreased expression of CTLA‐4 and GITR, as well as IL‐10 and TGF‐β, and impair its suppressive function. Mechanistic evidence showed that silencing of miR‐126 enhanced the expression of its target p85β and subsequently altered the activation of PI3K/Akt pathway, which was ultimately responsible for reduced induction and suppressive function of Tregs. Finally, we further revealed that miR‐126 silencing could impair the suppressive function of Tregs in vivo and endow effectively antitumour effect of CD8+T cells in adoptive cell transfer assay using a murine breast cancer model. Therefore, our study showed that miR‐126 could act as fine‐tuner in regulation of PI3K‐Akt pathway transduction in the induction and sustained suppressive function of Tregs and provided a novel insight into the development of therapeutic strategies for promoting T‐cell immunity by regulating Tregs through targeting specific miRNAs.